If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 3) = 6(2x + -5) Reorder the terms: 4(3 + x) = 6(2x + -5) (3 * 4 + x * 4) = 6(2x + -5) (12 + 4x) = 6(2x + -5) Reorder the terms: 12 + 4x = 6(-5 + 2x) 12 + 4x = (-5 * 6 + 2x * 6) 12 + 4x = (-30 + 12x) Solving 12 + 4x = -30 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 12 + 4x + -12x = -30 + 12x + -12x Combine like terms: 4x + -12x = -8x 12 + -8x = -30 + 12x + -12x Combine like terms: 12x + -12x = 0 12 + -8x = -30 + 0 12 + -8x = -30 Add '-12' to each side of the equation. 12 + -12 + -8x = -30 + -12 Combine like terms: 12 + -12 = 0 0 + -8x = -30 + -12 -8x = -30 + -12 Combine like terms: -30 + -12 = -42 -8x = -42 Divide each side by '-8'. x = 5.25 Simplifying x = 5.25
| -7/4c=-7 | | F(7)-f(4)/7-4 | | -18=2/3x | | 3(x+7)=6(-3+7x) | | -5/6d=5 | | (1.6x^3+4.9x^2-3.7x)-(-4.1x^3-4.8x^2+95)= | | Q=t/12 | | 0.5a-3=7-3/4a | | 5(2x-2)=5(x-1) | | 7u+5+18u+18=248 | | -7(2x-5)+5(3x-5)-2=6-9 | | 21+1.5h=10+2.75h | | (-1/6x^6)(-1/5x) | | -7(2x-5)+(3x-5)=6-9 | | 90=18y+30-5y-5 | | -2(3y-3)-y=-3(y-2) | | 5+c=8 | | 3=-3(11-s)/7 | | .3(8)+x=.5(8+x) | | 6y-14(-2y+8)=432 | | D=4m+9 | | 2.5+5.75=2+3.75a | | 4y=16-8x | | 3(2x-4)=32-5(x-2) | | 156=18x+21+8x+5 | | 2(3x+4)=-5(5x-3) | | -19-5x=-17x+17 | | 17x+x=-4x | | 7x-7=13+12y | | 17r+18=221-12r | | x^2+0x-1=01 | | y-5=6(x+4) |